Isodon lophanthoides alleviates liver fibrosis via modulation of purine metabolism and NF-κB signaling pathway: insights from multi-omics analysis - Chen, Kuikui; Liang, Jie; Tan, Yong; Li, Yaohua; Pan, Xiaojiao; Guo, Zhonghui; Zhang, Wentao; Sun, Zongxi (Frontiers in Pharmacology, 2025)
BackgroundIsodon lophanthoides, a core botanical drug in Yao ethnomedicine, has traditionally been used to treat jaundice-type hepatitis and cholecystitis. However, its therapeutic potential and mechanisms against liver fibrosis remain largely unexplored.MethodsThe metabolites of I. lophanthoides water extract (ILW) were characterized by ultra-performance liquid chromatography (UPLC) and UPLC coupled with quadrupole time-of-flight mass spectrometry (Q-TOF/MS). A carbon tetrachloride (CCl4)-induced liver fibrosis mouse model was employed to evaluate the anti-fibrotic effects of ILW. An integrated multi-omics approach encompassing transcriptomics, proteomics, and metabolomics was used to elucidate the underlying mechanisms, further supported by Western blotting, targeted metabolite quantification, and enzyme-linked immunosorbent assay (ELISA).ResultsThirty-two metabolites were identified in ILW. Among them, the concentrations of caffeic acid, rosmarinic acid, schaftoside, and isoschaftoside were determined to be 1.10, 5.13, 0.12, and 0.18 mg·g-1, respectively. ILW treatment significantly reduced serum levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), procollagen type III (PC-III), collagen type IV (COL-IV), laminin (LN), and hyaluronic acid (HA) in liver fibrotic mice. Histopathological analyses showed that ILW significantly alleviated liver inflammation, collagen deposition, and fibrosis. Multi-omics analysis revealed that ILW’s anti-fibrotic effects are linked to modulation of purine metabolism and inhibition of the nuclear factor kappa-B (NF-κB) signaling pathway. High-dose ILW lowered hepatic levels of adenine, adenosine monophosphate (AMP), and inosine monophosphate (IMP), while increasing adenosine, hypoxanthine, and N6-methyladenosine (m6A). Furthermore, high-dose and medium-dose ILW downregulated key NF-κB-related proteins, including toll-like receptor 4 (TLR4), myeloid differentiation primary response 88 (MyD88), phosphorylated NF-κB, transforming growth factor beta 1 (TGF-β1), tumor necrosis factor-alpha (TNF-α), interleukin-6 (IL-6), and interleukin-1 beta (IL-1β).ConclusionILW exerts protective effects against liver fibrosis by attenuating inflammation, fibrosis, and liver damage through modulation metabolism modulation and NF-κB pathway inhibition. These findings provide a scientific basis for the traditional use of I. lophanthoides in liver-related disorders.